THE IMPLEMENTATION OF COOPERATIVE LEARNING METHOD IN TEACHING SPEAKING SKILL : A Qualitative Descriptive Study of Tenth Grade Senior High School Students - Ria Armelia, - (2018)
Cooperative learning (CL) as a teaching method plays an important role in teaching learning process. It requires some principles and procedures to implement CL method in the classroom. The research was aimed at investigating the implementation of cooperative learning method in teaching speaking skill and the strengths and the weaknessess of using cooperative learning method in teaching speaking based on students' perspective. The research involved thirty-six students and one English teacher at a Senior High School in Cimahi. The source for data collection was classroom observation, interview and questionnaire. Using qualitative descriptive method, the results of the study indicate that by implementing cooperative learning, the learners had opportunities to develop their speaking ability. In addition, there are also two basic steps used by teacher in implementing CL in the classroom which are teacher's procedure in implementing cooperative learning in the classroom and the principles of cooperative learning in teaching speaking skill. Specifying the objectives for the lesson, structuring learning group, monitoring and evaluating students' performances were essential procedures in implementing CL in the classroom. Also, cooperative learning offers some benefits not only for the teacher but also for the students. It is shown from some strengths found in implementing cooperative learning namely (1) developing students' social skill, (2) increasing students' motivation, and (3) engaging students in speaking skill. Thus, it can be concluded that the students' responses towards cooperative learning were positive. ;--Pembelajaran kooperatif (CL) sebagai metode mengajar berperan pernting dalam proses pembelajaran. Pembelajaran kooperatif memerlukan beberapa prinsip dan prosedur untuk diterapkan di kelas. Penelitian" ini bertujuan untuk mengetahui implementasi metode cooperative learning dalam pengajaran kemampuan berbicara dan serta kelebihan dan kelemahan dalam menggunakan metode cooperative learning berdasarkan perspektif siswa. Penelitian ini melibatkan tiga puluh enam siswa dan satu guru bahasa Inggris di salah satu sekolah menengah atas yang ada di kota Cimahi. Sumber pengumpulan data penelitian yaitu melalui observasi kelas, pembelajaran kooperatif meliputi dua tahapan penting, yaitu prosedur guru dalam mengimplementasikan metode cooperative learning di kelas dan prinsip-prinsip cooperative learning dalam pengajaran kemampuan berbicara. Selain itu, menetapkan tujuan pembelajaran, menata kelompok belajar, memantau dan mengevaluasi kinerja siswa sangat penting dalam menerapkan metode cooperative learning di kelas. Selain itu, pembelajaran kooperatif memiliki beberapa kelebihan tidak hanya untuk guru tetapi juga untuk siswa. Hal itu ditunjukan dari beberapa kelebihan yang ditemukan dalam pengimplementasian metode cooperative learning. Sehingga, dapat disimpulkan bahwa respon siswa terhadap pembelajaran cooperative learning sangatlah positif.